EVALUASI SISTEM PENGENDALIAN INTERNAL TERHADAP PENGELUARAN KAS: (STUDI KASUS PADA KPRI INSKO DINAS KOPERASI DAN UKM PROVINSI SUMATERA UTARA) - Laksamana Aru Sulaiman; Imsar; Rahmat Daim Harahap (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the implementation, evaluation results, and evaluation of the internal control system evaluation constraints on cash disbursements at KPRI INSKO Cooperatives and SMEs Office of North Sumatra Province. The types of data used in this research are qualitative and quantitative, with primary and secondary data sources. The research approach in this study is descriptive qualitative research with a comparative method (comparison) between the theory of elements of internal control on cash disbursements and their implementation. The instruments in this study were observation, interviews, and documentation. The data analysis technique in this research is comparativequalitative descriptive. The results showed that the internal control system for cash disbursements at KPRI INSKO Cooperatives and SMEs Office of North Sumatra Province was still not running well and not in accordance with the elements of the theory of the internal control system for cash disbursements, namely there are functions, procedures, and related documents that is in accordance with the theory in internal control of cash disbursements, and only uses the cash flow statement. There are also problems that there is no direct examination of the cash function, and the supervisory body has not used an independent party. The implication of this research for KPRI INSKO Cooperatives and SMEs Office of North Sumatra Province is that the implementation of the internal control system for cash disbursements can run better and maximally, so that the initial goals of the cooperative can be achieved.